The Financial Impact of Different Stormwater Fee Types: A Case Study of Two Municipalities in Virginia. (27th October 2017) - Fedorchak, Amanda; Dymond, Randel; Campbell, Warren
Abstract: Eight stormwater user fees (SUFs) were applied to the City of Roanoke and the Town of Blacksburg, Virginia, to determine the effect each has on how land use type impacts the sources of revenue. Roanoke is larger and includes more industrial areas, but less multifamily impervious areas than Blacksburg, which translates differently in the SUFs. Residential parcels comprise the highest percentage of the revenue in all eight SUFs in Blacksburg and four in Roanoke. For both municipalities, two specific SUFs consistently comprised the highest percentage burden for residential homeowners while three other SUFs demonstrated the highest burden for commercial parcels. Open space parcels contain little impervious area, yet account for up to 27% of the revenue in the Blacksburg Area fee structure. Industrial parcels comprise more revenue in Roanoke, averaging 10.1‐4.5% in Blacksburg. Fee types that are easier to administer ( e.g ., Flat fees) may not fully represent the stormwater contribution from the parcels. SUF types that more accurately represent the stormwater burden on the municipality are also more administratively intensive and are more variable with fee factors.